Knowledge Management in Higher Education in Nepal: Current Practices, Challenges, and Future Prospects - Subedi, Pushparaj (TULSSAA Journal, 2025)
Higher Education Institutions (HEIs) serve as centers for knowledge creation, dissemination, and application, significantly contributing to academic advancement and societal development. Effective Knowledge Management (KM) plays a pivotal role in enhancing decision-making, fostering innovation, and ensuring institutional competitiveness (Nonaka & Takeuchi, 1995). Despite notable growth in Nepal's higher education sector, challenges such as fragmented knowledge systems, inadequate digital infrastructure, and policy gaps continue to hinder optimal knowledge utilization. This paper explores the current state of KM practices in Nepalese higher education and highlights opportunities to create a knowledge-driven academic environment. Implementing robust KM strategies can transform traditional academic environments by promoting knowledge sharing, research collaboration, and efficient resource management. Furthermore, KM strengthens institutional performance by aligning higher education institutions with global academic standards and fostering organizational excellence (Kara & DeShields, 2004; Cranfield & Taylor, 2008). However, the absence of a comprehensive KM framework tailored to Nepalese higher education poses a critical barrier to achieving these outcomes. This study emphasizes the need for strategic KM adoption to enhance research productivity, improve teaching methodologies, and facilitate knowledge dissemination. Addressing these challenges through policy interventions, digital infrastructure development, and capacity-building initiatives will drive sustainable academic growth and institutional excellence in Nepal’s higher education sector.